Multimodality registration of two-dimensional echocardiography and cardiac CT for mitral valve diagnosis and surgical planning - Khalil, A; Faisal, A; Ng, SC; Liew, YM; Lai, KW (Spie-Soc Photo-Optical Instrumentation Engineers, 2024)
Indexed by WOS/ Scopus